2021
DOI: 10.1093/jn/nxab107
|View full text |Cite
|
Sign up to set email alerts
|

Low Circulating Vitamin D in Intensive Care Unit–Admitted COVID-19 Patients as a Predictor of Negative Outcomes

Abstract: Background Vitamin D deficiency has been associated with an increased risk of respiratory infections. Objectives The study aimed to evaluate the serum 25-hydroxyvitamin D [25(OH)D] concentration in patients admitted to the intensive care unit (ICU) as a predictor of coronavirus disease 2019 (COVID-19) mortality. Methods A single-center retrospective observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 49 publications
1
11
0
11
Order By: Relevance
“…Vitamin D is postulated to play an important immunomodulatory role, and deficiency is associated with increased incidence of ARVI, including COVID-19 [ 26 , 27 , 28 ]. Our previous results also showed that severe vitamin D deficiency is associated with severity and death in COVID-19 patients [ 29 ], and were comparable to recent findings [ 4 , 30 ]. Dissanayake and colleagues, whose meta-analysis included 72 COVID-19 observational and 4 interventional randomized studies, have shown not only correlations between 25(OH)D level and severity or mortality, but also some clinical benefits and improvement in inflammatory markers of vitamin D supplementation in treating COVID-19 [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D is postulated to play an important immunomodulatory role, and deficiency is associated with increased incidence of ARVI, including COVID-19 [ 26 , 27 , 28 ]. Our previous results also showed that severe vitamin D deficiency is associated with severity and death in COVID-19 patients [ 29 ], and were comparable to recent findings [ 4 , 30 ]. Dissanayake and colleagues, whose meta-analysis included 72 COVID-19 observational and 4 interventional randomized studies, have shown not only correlations between 25(OH)D level and severity or mortality, but also some clinical benefits and improvement in inflammatory markers of vitamin D supplementation in treating COVID-19 [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite vaccination rollouts, much focus has been documented on additional preventive measures such as using vitamin D supplementation to be promising in COVID-19 [7,8]. While strong observational evidence [9][10][11] indicate the association of low vitamin D levels to the COVID-19 susceptibility, severity and mortality outcomes, the beneficial use of vitamin D supplements in COVID-19 has been reported in some non-randomized observational cohorts [12,13]. However, there is still a scarcity of information through randomized controlled trials (RCTs) on the use of vitamin D supplementation in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Выявленные статистически значимые различия в концентрации витамина Д у пациентов с инфекцией и без инфекции указывают на его протективную роль при бактериальной инфекции и сепсисе [23]. Кроме этого, концентрация витамина Д менее 10 нг/мл является независимым предиктором неблагоприятного исхода у пациентов с тяжелым течением COVID-19 [24].…”
Section: материал и методыunclassified